RANCANG BANGUN E-LEARNING BERBASIS GAMIFIKASI DAN LEARNING STYLE PEMBELAJAR UNTUK OPTIMALISASI HASIL BELAJAR: DESIGN AND DEVELOPMENT E-LEARNING BASED ON GAMIFICATION AND LEARNER LEARNING STYLE TO OPTIMIZE LEARNING OUTCOME - Andang Wijanarko; Endina Putri Purwandari; Febrian Solikhin (LPPM Universitas Abdurrab, 2026)
The adoption of e-learning has been becoming crucial in modern education by offering flexibility, accessibility, and scalability for learners. However, many e-learning platforms still adopt a “one-size-fits-all” approach that ignores the differences in individual learner characteristics, especially learning styles. This lack of personalization often leads to a lack of motivation that ends in suboptimal learning outcomes. This study aims to design and develop an e-learning platform by integrating gamification elements and learning styles to optimize user learning outcomes. The research method uses a Research and Development (R&D) approach and the ADDIE model which includes five stages: analysis, design, development, implementation, and evaluation. This system combines general and specific gamification features according to the VARK learning style model. The system's effectiveness was tested on 67 students in the Computer and Programming course who were divided into experimental and control groups. The evaluation results showed significant differences in learning outcomes in the experimental group compared to the control group. In addition, the results of the independent t-test showed a significant difference (p < 0.05) in learning outcomes between the experimental and control groups. This means that the implementation of a gamification-based e-learning system and learning style features significantly impacts learning outcomes, especially compared to e-learning without learning style features. This study confirms that integrating gamification elements and learning styles positively enhances the learning experience. Furthermore, the integration of these two approaches has been proven to provide a meaningful learning experience and encourage learners to maintain their participation.